2020
DOI: 10.1002/gps.5271
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime history of traumatic brain injury is associated with increased loneliness in adults: A US nationally representative study

Abstract: Background/Objectives An estimated 55 million individuals worldwide live with chronic disability associated with traumatic brain injury (TBI), which may include cognitive, behavioral, and social impairments. Reduced participation in social activities is common after TBI; however, few studies have evaluated loneliness among survivors of TBI. The current study aimed to evaluate the association between history of TBI and loneliness and to identify mediators of this association. Methods/Design Retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
(137 reference statements)
0
11
0
Order By: Relevance
“…We characterized participants’ time in various locations, social contexts, and activities as they went about their daily lives. TBI is associated with reduced community mobility and increased risk of loneliness and social isolation (Kumar et al, 2020; Ponsford et al, 2014). Our group-level findings comport with prior studies suggesting that people with moderate–severe TBI spend much of their time at home (Lenaert et al, 2019) and alone (Winkler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We characterized participants’ time in various locations, social contexts, and activities as they went about their daily lives. TBI is associated with reduced community mobility and increased risk of loneliness and social isolation (Kumar et al, 2020; Ponsford et al, 2014). Our group-level findings comport with prior studies suggesting that people with moderate–severe TBI spend much of their time at home (Lenaert et al, 2019) and alone (Winkler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Social needs outweigh the physical and cognitive needs in ranking of importance by both survivors themselves and their families. These findings have been demonstrated and replicated within an international contextand a recent study in the United States (US) found that history of brain injury was associated with greater loneliness compared with individuals without brain injury in a representative sample of US adults (Kumar et al, 2020). They recommended that treating depressive symptoms and medical consequences of brain injury may be a target to ameliorate reporting of loneliness in this population.…”
Section: Introductionmentioning
confidence: 75%
“…Though we did not observe population-level differences in mood by pandemic exposure in our study, mental health should still be continually monitored in TBI populations moving forward. Individuals with moderate-to-severe TBI already struggle with anxiety [ 49 ], loneliness [ 50 ], and limited social participation compared to non-injured peers [ 51 , 52 ]. These daily challenges would likely only worsen during a global pandemic due to fear of contracting the virus and recommendations or mandates to limit in-person social interaction.…”
Section: Discussionmentioning
confidence: 99%